PBG-WaveNet: Probabilistic buoy-to-grid reconstruction and forecasting of significant wave height fields from sparse buoy observations - Nan Wang; Shangfei Lin; Chuang Liu; Mukun Chen; Zaijin You (Ocean Engineering, 2026)

Examinations of Surface Waves and Ocean Circulation During Severe Weather Conditions over the Northwest Atlantic Using a Coupled Wave–Current Modelling System: An Overview - Jinyu Sheng; Qiantong Pei; Shangfei Lin; Colin Hughes (Journal of Marine Science and Engineering, 2025)
Upper oceans are highly energetic during a severe weather event, with large surface waves and intense ocean currents over areas affected by the storm. An advanced and coupled wave–current modelling system for the northwestern Atlantic (WCMS-NWA) was developed by the Regional Modelling Group at Dalhousie University for simulating surface waves and three-dimensional ocean currents over the eastern Canadian shelf and adjacent waters. Applications of this modelling system during different weather events have been discussed separately in the past. In this overview, the model performances of WCMS-NWA and major hydrodynamics over the study region during 11 severe storms are summarized. Comparisons of model results with in situ oceanographic observations and satellite data demonstrate the suitability and accuracy of WCMS-NWA in simulating ocean circulation and surface waves during normal weather conditions and intense ocean currents and extreme surface waves during severe storm events. It is shown that satisfactory model performance of WCMS-NWA requires reliable temporal–spatial representations of atmospheric forcing and inclusions of interactions between waves and currents (WCIs). Important contributions from WCIs during these severe weather conditions are discussed based on the model results.

The synergistic effect of pulsed red light and leonurus inhibits primary dysmenorrhea induced by oxytocin in mice by modulating calcium signaling and inhibiting inflammatory responses - Qiqi Fu; Hui Jiang; Jiali Yang; Haokuan Qin; Longfei Huo; Yi Ren; Shangfei Lin; Muqing Liu; Jinghui Yao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Convergence and divergence of storm waves induced by multi-scale currents: Observations and coupled wave-current modeling - Shangfei Lin; Jinyu Sheng; Jinhai Zheng; Aifeng Tao (Coastal Engineering, 2024)

Future changes in intense tropical cyclone hazards in the Pearl River Delta region: an air-wave-ocean coupled model study - Zhenning Li; Jimmy C. H. Fung; Mau Fung Wong; Shangfei Lin; Fenying Cai; Wenfeng Lai; Alexis K. H. Lau (Natural Hazards, 2024)
The Pearl River Delta (PRD) region is highly vulnerable to tropical cyclone (TC)-caused coastal hazards due to its long and meandering shoreline and well-developed economy. With global warming expected to continue or worsen in the rest of the twenty-first century, this study examines the TC impact on the PRD coastal regions by reproducing three intense landfalling TCs, namely Vicente (2012), Hato (2017), Mangkhut (2018), using a sophisticated air-wave-ocean coupled model of high spatial resolution (1-km atmosphere and 500-m wave and ocean). The simulations are conducted using present-day reanalysis data and the same TCs occurring in a pseudo-global warming scenario projected for the 2090s. Results indicate that the coupled model accurately reproduces the air-wave-ocean status during the TC episodes. The 2090s thermodynamic status effectively increases the intensity of intense TCs, leading to more severe coastal hazards including gale, rainstorm, and storm surges and waves. On average, the maximum surface wind speed within 50–200 km to the right of the TC center can increase by 4.3 m/s (+22%). The 99th and the 99.9th percentile of accumulated rainfall will increase from 405 to 475 mm (+17.3%), and from 619 to 735 mm (+18.6%), respectively. The maximum significant wave height at the ocean is lifted by an average of 57 cm (+13.8%), and the coastline typically faces a 40–80 cm increase. The maximum storm surges are lifted by 30–80 cm over the open sea but aggravate much higher along the coastline, especially for narrowing estuaries. For Typhoon Vicente (2012), there is more than a 200 cm wave height increase observed both at open sea and along the coastline. In the 2090s context, a combination of mean sea level rise, storm surge, and wave height can reach more than 300 cm increase in total water level at certain hot-spot coastlines, without considering the superposition of spring tides.

Interactions between Surface Waves, Tides, and Storm-Induced Currents over Shelf Waters of the Northwest Atlantic - Shangfei Lin; Jinyu Sheng (Journal of Marine Science and Engineering, 2023)
A coupled wave–tide–circulation model is used to investigate wave–current interactions (WCIs) over the shelf waters of the Northwest Atlantic (NWA) during Hurricane Earl (2010). WCIs have substantial impacts on hydrodynamics in the upper ocean. The significant wave heights are modulated by WCIs, particularly over regions with strong current gradients, with a reduction up to ~2.1 m (20%) during the storm. Noticeable decreases in surface elevations and tidal currents occur in regions with strong tides such as the Gulf of Maine, mainly due to the wave-enhanced bottom stress. Over regions with weak tidal currents, wave effects on currents are dominated by two competitive processes between wave-induced forces and wave-enhanced mixing. The former strengthens surface currents (up to ~0.55 m/s) and increases the peak storm surge (up to ~0.48 m). The latter is responsible for the reduction in storm-induced surface currents (up to ~0.94 m/s) and anticyclonic modulation of current directions. Vertically, WCIs extend the strong vertical current shear and shift it downward during the storm, which enhances the local mixing and changes the structures of near-inertial oscillations (NIOs). Moreover, tidal currents also change the magnitudes of the NIOs and subtidal currents and affect the intensity of WCIs.